2012
DOI: 10.1002/jcp.23040
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIIIA transglutaminase expression and secretion by osteoblasts is regulated by extracellular matrix collagen and the MAP kinase signaling pathway

Abstract: Osteoblast differentiation is regulated by the presence of collagen type I (COL I) extracellular matrix (ECM). We have recently demonstrated that Factor XIIIA (FXIIIA) transglutaminase (TG) is required by osteoblasts for COL I secretion and extracellular deposition, and thus also for osteoblast differentiation. In this study we have further investigated the link between COL I and FXIIIA, and demonstrate that COL I matrix increases FXIIIA levels in osteoblast cultures and that FXIIIA is found as cellular (cFXII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Expression in bone and esophagus was additionally revealed by the immunohistochemical analysis. Studies in mammals reported that FXIII is expressed in osteoblasts, chondrocyte, and preadipocyte cells [10][11][12], which is consistent with our present data. Our results support that FXIIIA plays multiple roles at several tissues including bone, while a recent report described that FXIIIA is not functionally expressed in bone [26].…”
Section: Discussionsupporting
confidence: 93%
“…Expression in bone and esophagus was additionally revealed by the immunohistochemical analysis. Studies in mammals reported that FXIII is expressed in osteoblasts, chondrocyte, and preadipocyte cells [10][11][12], which is consistent with our present data. Our results support that FXIIIA plays multiple roles at several tissues including bone, while a recent report described that FXIIIA is not functionally expressed in bone [26].…”
Section: Discussionsupporting
confidence: 93%
“…1B; the data shows that not all stainable FXIII-A is found to co-localize with Cav-1. The induction of FXIII-A upon differentiation treatment (DM media) was consistent with that observed in our previous studies (Al-Jallad et al 2011;Piercy-Kotb et al 2012;Wang et al 2014). …”
Section: Fxiii-a Associates With Caveolae In Differentiating Osteoblastssupporting
confidence: 91%
“…Moreover, the down-regulation of TG2 inhibited angiogenesis in cell culture (36). In addition, osteoblast differentiation is regulated by the presence of collagen type I in the ECM, and TGase is required for collagen secretion and extracellular deposition, which controls osteoblast differentiation (37). TG2 can also associate with several ECM proteins and mediate interactions between the ECM and soluble growth factors through the regulation of integrins and growth factor receptors (38,39).…”
Section: Discussionmentioning
confidence: 99%